Karakteristik fisik dan komposisi kimia minyak kayu putih (Melaleuca cajuputi) asal Maluku dan Nusa Tenggara Barat [Physical characteristics and chemical composition of eucalyptus oil (Melaleuca cajuputi) from Maluku and West Nusa Tenggara] - Rienoviar, Rienoviar; Smith, Husein; Assagaf, Muhammad; Pongtuluran, Olivia Bunga; Agustinisari, Iceu; Harimurti, Niken (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2024)
Eucalyptus oil is an essential oil popular in Indonesia due to its ability to treat flatulence, induce a sense of warmth, and serve as an antibacterial, antiviral, antifungal, and aromatherapy agent. Melaleuca cajuputi is a species of eucalyptus plant that yields eucalyptus oil. This plant is commonly found in Central Maluku and West Nusa Tenggara. The distilling process of eucalyptus oil took four hours and involved using steam distillation. Several physical parameters, including cineole content, oil weight, specific gravity, optical rotation, and ethanol solubility, were utilized to evaluate the grade of the produced eucalyptus oil. The analysis of physical properties was conducted using SNI 06-3954-2006-compliant methodologies. The volatile compounds of eucalyptus oil were analyzed using the Gas Chromatography-Mass Spectrometry (GC-MS) technique. The test results indicated that the purity of eucalyptus oil from Maluku and NTB specifically met the requirements of SNI 06-3954-2006. GC-MS measurement revealed that eucalyptus oil from Maluku, with a yield of 1.42%, contained 26 chemical components, with 1.8-cineole comprising the highest percentage at 67.38%. In contrast, the yield of NTB eucalyptus oil was 1.84%, and it contained 21 volatile compounds of which the compound of 1.8 cineole made up 66.58% of the component composition